Dinoflagellates from Pucusana( Dept. and Prov. Lima) - Solé A., Mireia (1974)
Nineteen species of marine Dinoflagelates are listed from Pucusana, Department of Lima, Peru. These be long to the following genera: Prorocentrum (1 sp.), Dinophysis (3 spp.), Pyrocystis (1sp.), Gonyaulax (2 spp.), Peridinium (8 spp.) and Ceratium (5 spp.). Five of them were not listed in published records for Peru.